MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA MELALUI BERMAIN PERAN DALAM TALK SHOW DI SMA - Wijayanti, Fransisika Dwi Mulyani (Jurnal Pembelajaran Prospektif, 2017)
The purpose of this research was to know the increased proportion of theachievement through playing a role on the talk shows for the XII IPS2 class ofSMAN 4 Pontianak. The samples of the research were 32 students of XII IPS2SMAN4 Pontianak. The findings of this study were improving students' English speaking skills in expressing opinions, soliciting opinions, agreeing and disapproving of opinions that had increased from the first cycle till the third one. The average value in the first cycle was 42.1; in second cycle was 48.16; and in the third cycle was 56.03. The level of achievement of the students' speaking skills increased as the effects of the application of role playing in talk shows; from a sufficient level to a good level, reflected through the increase from the first cycle to the third one. The process of teaching and learning on speaking skills, especially in expressing opinions, expressing agreement and disagreementthrough role play on talk shows affected active roles on the students inspeaking English. This technique also provided an opportunity for students toexpress their opinions spontaneously and freely.